When McKinsey comes to town the hidden influence of the world's most powerful consulting firm - Bogdanich, Walt; Forsythe, Michael (New York Doubleday, 2022)
"A book about the McKinsey Consulting company and their impact on businesses"--
Introduction: When McKinsey comes to town -- Wealth without guilt: McKinsey's values -- Winners and losers: the inequality machine -- Playing both sides: helping government help McKinsey -- McKinsey at ICE: "We do execution, not policy" -- Befriending China's government -- Guarding the Gates of Hades: tobacco and vaping -- Turbocharging opioid sales -- "Turning a coal mine into a diamond" -- Toxic debt: McKinsey on Wall Street -- Allstate's secret slides: "Winning will be a zero-sum game" -- "The Enron Astros" -- "Clubbing seals": the South Africa debacle -- Serving the Saudi state -- Chumocracy: half a century at Britain's NHS.
Includes bibliographical references and index.
110911
Keywords: McKinsey and Company -- Influence; Industrial management; Business consultants; Business & Economics / General; Influence (Literary, artistic, etc.)